Coordinated precoding techniques for multi-cell MISO-OFDM networks - Holakouei, Reza
The aim of this manuscript is to propose and compare several distributed linear precoding schemes for the downlink of multicell MISO-OFDM based systems. The precoder vectors are computed in a distributed manner at each BS, assuming that the BSs have only knowledge of local channel state information and considering several criteria: distributed zero-forcing (DZF), maximum ratio transmission and distributed virtual signal-to-interference noise ratio (DVSINR). Then the system is further optimized through centralized power allocation. Two centralized power allocation algorithms with per-BS power constraint and different complexity tradeoffs are proposed: namely, minimization of the instantaneous average BER and minimization of the sum of inverse of signal-to-interference noise ratio, for which a closed-form power allocation scheme is derived. The performance of the proposed schemes is compared considering typical pedestrian scenarios based on LTE specifications. The numerical results show that increasing the number of degrees of freedom or for high SNR, the proposed DZF approaches tends to the DVSINR based ones.